Molecular analysis of GCN3, a translational activator of GCN4: evidence for posttranslational control of GCN3 regulatory function. - Hannig, E M (1988)
GCN4 encodes a transcriptional activator of amino acid biosynthetic genes in Saccharomyces cerevisiae. The GCN3 product is a positive regulator required for increased synthesis of GCN4 protein in amino acid-starved cells. GCN3 appears to act indirectly by antagonizing GCD-encoded negative regulators of GCN4 expression under starvation conditions; however, GCN3 can also suppress the effects of gcd12 mutations under nonstarvation conditions. These results imply that the GCN3 product can promote either repression or activation of GCN4 expression depending on amino acid availability. We present a complete physical description of the GCN3 gene and its transcript, plus measurements of GCN3 expression at the transcriptional and translational levels under different growth conditions. GCN3 encodes a 305-amino-acid polypeptide with no significant homology to any other known protein sequence. GCN3 mRNA contains no leader AUG codons, and no potential GCN4 binding sites were found in GCN3 5' noncoding DNA. In accord with the absence of these regulatory sequences found at other genes in the general control system, GCN3 mRNA and a GCN3-lacZ fusion enzyme are present at similar levels under both starvation and nonstarvation conditions. These data suggest that modulation of GCN3 regulatory function in response to amino acid availability occurs posttranslationally. A gcn3 deletion leads to unconditional lethality in a gcd1-101 mutant, supporting the idea that GCN3 is expressed under normal growth conditions and cooperates with the GCD1 product under these circumstances to carry out an essential cellular function. We describe a point mutation that adds three amino acids to the carboxyl terminus of GCN3, which inactivates its positive regulatory function required under starvation conditions without impairing its ability to promote functions carried out by GCD12 under nonstarvation conditions.